Comparing pre-operative versus post-operative single and multi-fraction stereotactic radiotherapy for patients with resectable brain metastases. (January 2023) - Perlow, Haley K.; Ho, Cindy; Matsui, Jennifer K.; Prasad, Rahul N.; Klamer, Brett G.; Wang, Joshua; Damante, Mark; Upadhyay, Rituraj; Thomas, Evan; Blakaj, Dukagjin M.; Beyer, Sasha; Lonser, Russell; et al.
Highlights: Pre-operative radiation therapy for brain metastases may reduce meningeal disease. Pre-operative radiation therapy for brain metastases may reduce radionecrosis. Fractionated radiation therapy for brain metastases may reduce local failure. Fractionated pre-operative radiation therapy requires prospective validation. Abstract: Background: The standard treatment for patients with large brain metastases and limited intracranial disease is surgical resection and post-operative stereotactic radiosurgery (SRS). However, post-operative SRS still has elevated rates of local failure (LF) and is complicated by radiation necrosis (RN), and meningeal disease (MD). Pre-operative SRS may reduce the risk of RN and MD, while fractionated therapy may improve local control through delivering a higher biological effective dose. We hypothesize that pre-operative fractionated stereotactic radiation therapy (FSRT) will have less toxicity compared to patients who receive post-operative SRS or FSRT. Methods: A multi-institutional analysis was conducted and included patients who had surgical resection and stereotactic radiation therapy to treat at least one brain metastasis. Pertinent demographic, clinical, radiation, surgical, and follow up data were collected for each patient. The primary outcome was a composite endpoint defined as patients with one of the following adverse events: 1) LF, 2) MD, and/or 3) Grade 2 or higher (symptomatic) RN. Results: 279 patients were eligible for analysis. The median follow-up time was 9 months. 87 % of patients received fractionated treatment. 29 % of patients received pre-operative treatment. The composite endpoint incidences for post-operative SRS (n = 10), post-operative FSRT (n = 189), pre-operative SRS (n = 27), and pre-operative FSRT (n = 53) were 0 %, 17 %, 15 %, and 7.5 %, respectively. Conclusions: In our study, the composite endpoint of 7.5% for pre-operative FSRT compares favorably to our post-operative FSRT rate of 17%. Pre-operative FSRT was observed to have low rates of LF, MD, and RN. Prospective validation is needed.